A palmar pressure sensor for measurement of upper limb weight bearing by the hands during transfers by paraplegics. (October 2013) - Kunju, Nissan; Ojha, Rajdeep; Devasahayam, Suresh R.
Abstract Paraplegic patients have to effect transfer from one seat to another by using their upper limbs. In this process the hands bear almost the entire weight of the body in at least some phases of the transfer. It is desirable to train patients, especially those who are elderly and otherwise weak, to distribute their weight so as to avoid large forces being sustained on any one hand for an extended period. It is also desirable to evaluate the effectiveness of assistive devices like lower limb FES in sharing the load on the hand. This study presents a simple and versatile method of measuring palmar hand force during transfers by paraplegic patients. It is important that this force sensor should not interfere with the grasping and stabilizing properties of the hands and should permit normal transferring. The force sensor comprises an air-filled pouch or pillow that can be placed on any surface. This pneumatic sensor feels like upholstery padding on the surface on which it is placed. The sensor integrates the total pressure applied to the surface of the pouch, thereby obtaining the total force exerted by the palm/hand. The fabrication of the sensor is described, as well as the associated measurement circuit. The static calibration shows that the sensor is linear up to 350 N and the dynamic calibration shows that it has a bandwidth of 13 Hz. The sensor was fabricated using an inflated inelastic airbag attached to a pressure transducer. An automatic offset correction circuit in the preamplifier module ensures that any offset due to initial pressure or sensor drift is removed and the output is zero under no load condition. The key to this sensor arrangement is the ease of fitting it into the intended location without disturbing the existing arrangement for the subject's activities of daily living (ADL).